Homogeneous‐to‐Heterogeneous‐Strategy Enables Multifunctional Phase‐Change Materials for Energy Storage. Issue 29 (7th April 2022) - Liu, Changhui; Zhang, Tianjian; Li, Tingsong; Wang, Yafei
Abstract: Functional phase‐change materials (PCMs) are conspicuously absent in various organic or inorganic solids with diversified applications in which the attributes of these molecular materials have been highly realized. Leakage problem during the phase transition process is the main obstacle on the way of widely use of solid‐liquid PCMs who has been recognized to be promisingly practical candidates for energy storage owing to the high energy storage density and small volume change in the phase transition process. Herein, a novel homogeneous‐to‐heterogeneous‐strategy, in which all the starting materials involved display a homogeneous state and the encapsulation framework formed in situ in the encapsulation process, enabled by an aerogel reaction of silica was realized under the catalysis of an organic base. Besides the comprehensive study upon energy storage performance, light‐to‐thermal conversion and recyclability performance study of the obtained materials reveal the clear superiority over pristine paraffin wax (PW) thanks to the versatility and robustness of this fabrication method. More importantly, the homogeneous‐to‐heterogeneous‐strategy endows a unique adsorption ability with respect to organic pollutant due to the PCMs inside and therefore bearing a great potential to be used in environment protection fields. Abstract : Homogenous‐to‐heterogenous‐strategy was raised as a concept to enable the fabrication of multifunctional phase change materials (PCMs). The as‐prepared PCM was endowed with enhanced thermal performance, shape flexibility, and organic pollutant removing function. This novel strategy is expected to be one of universal PCMs encapsulation method.